FOOD SECURITY: TOPICALITY FOR RUSSIA - G. V. Podbiralina; T. E. Migaleva; A. V. Ryzhakova; N. Р. Savina (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
Analyzing food security state is one of the most important lines, which is examined in detail in economic literature. It is stipulated mainly by the fact that food security standing shows the ability of the agro-industrial complex to provide the population with foods and at the same time to support the balanced and optimal correlation between home production and imported food. The goal of the article is to analyze food security standing in Russia and the world. The authors defined the essence of the notion ’food security’, identified criteria, which provide an opportunity to find out the level of the problem. On the basis of reports and analytical materials of international organizations, the Ministry of agriculture RF, research by Russian and overseas experts the authors came to the conclusion about the level of food security in Russia, identified the problems of agriculture development and food security and put forward ways of their resolving.